2016
DOI: 10.17511/jopm.2016.i02.03
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and resistance pattern of bacterial isolates from pus samples in a tertiary care hospital, Karimnagar

Abstract: Background: Wound infection can cause delayed healing, chronicity which indirectly causes financial burden and psychological stress on patients. Aim: To speciate the organism isolated from pus sample received and its antibiotic sensitivity test. Methods and materials: All isolated organism are identified by colony morphology, Gram stain and biochemical reactions. Antibiotic sensitivity test for all isolates were done by Kirby-Bauer method using Mueller Hinton agar. Results: The major contribution of sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Pyrogenic infections that are characterised by local and systemic inflammations can be either due to single organism or multiple pathogens. The study revealed that 84.2% (112 samples) were positive for the isolation of pathogens from pus samples that was higher compared to the reports of [18]. The aetiological agents include Gram positive and Gram negative bacteria like Staphylococcus aureus, Enterococci, Pseudomonas aeruginosa, Escherichia coli, Klebsiella sps and Proteus sps.…”
Section: Discussionmentioning
confidence: 68%
“…Pyrogenic infections that are characterised by local and systemic inflammations can be either due to single organism or multiple pathogens. The study revealed that 84.2% (112 samples) were positive for the isolation of pathogens from pus samples that was higher compared to the reports of [18]. The aetiological agents include Gram positive and Gram negative bacteria like Staphylococcus aureus, Enterococci, Pseudomonas aeruginosa, Escherichia coli, Klebsiella sps and Proteus sps.…”
Section: Discussionmentioning
confidence: 68%